2018
DOI: 10.1038/s41598-018-19528-2
|View full text |Cite
|
Sign up to set email alerts
|

Motor signatures of emotional reactivity in frontotemporal dementia

Abstract: Automatic motor mimicry is essential to the normal processing of perceived emotion, and disrupted automatic imitation might underpin socio-emotional deficits in neurodegenerative diseases, particularly the frontotemporal dementias. However, the pathophysiology of emotional reactivity in these diseases has not been elucidated. We studied facial electromyographic responses during emotion identification on viewing videos of dynamic facial expressions in 37 patients representing canonical frontotemporal dementia s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 82 publications
(121 reference statements)
0
17
1
Order By: Relevance
“…For FTD patients, portions of the frontal and anterior parts of the temporal lobes atrophy (Warren, Rohrer, and Rossor 2013). Patients who were once empathic have trouble recognizing emotions in others, and the facial mimicry essential for making sense of others' emotions becomes severely impaired (Goodkind et al 2015;Marshall et al 2018). Patients also become much less prosocial, both in terms of sharing resources with others and of helping others in need (Sturm et al 2017).…”
Section: A Putative Model Of the Neurobiology Of Wisdommentioning
confidence: 99%
“…For FTD patients, portions of the frontal and anterior parts of the temporal lobes atrophy (Warren, Rohrer, and Rossor 2013). Patients who were once empathic have trouble recognizing emotions in others, and the facial mimicry essential for making sense of others' emotions becomes severely impaired (Goodkind et al 2015;Marshall et al 2018). Patients also become much less prosocial, both in terms of sharing resources with others and of helping others in need (Sturm et al 2017).…”
Section: A Putative Model Of the Neurobiology Of Wisdommentioning
confidence: 99%
“…This variability maps onto separable clinicoanatomical subsyndromes of bvFTD, 16,51 albeit with extensive overlap in individual patients. Among these, the syndrome associated with focal right temporal lobe atrophy is especially striking, with profound loss of emotional reactivity and awareness, hypochondriasis, topographical difficulties and sometimes unusual phenomena such as hyperreligiosity, hallucinations, and cross-modal sensory experiences; 52 inability to recognize familiar faces (prosopagnosia) may be a leading feature, as part of a more general failure of social signal processing which also extends to abnormal physiological responses, 53 and as the syndrome evolves it overlaps increasingly with svPPA. Where MRI in bvFTD is initially inconclusive, serial MRI studies at a yearly interval may document progressive brain atrophy and corroborate a clinical impression of deterioration.…”
Section: Behavioral Variant Ftdmentioning
confidence: 99%
“…In addition, there is growing awareness of the systemic metabolic and physiological correlates of deranged homeostatic processing in FTD. 91,92 Complementary tools derived from functional neuroimaging, autonomic, and electrophysiology 39,53,88,93 address neural network dysfunction and may yield proxies of complex clinical phenotypes that are difficult to measure directly. Multimodal biomarkers combining these different measures may provide the most sensitive and specific pathophysiological indices of underlying pathogenic protein activity.…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that emotion recognition and perspective-taking, forms of “cognitive empathy,” are impaired in bvFTD and reflect atrophy in the temporal pole, lateral temporoparietal cortex, and medial prefrontal cortex ( 22 29 ). Poor emotion recognition in bvFTD may be due, in part, to impairments in “emotional empathy” ( 24 , 26 , 30 , 31 ), an automatic, primitive form of affect-sharing that facilitates emotion recognition ( 20 , 32 , 33 ). During emotional empathy, emotions travel rapidly across individuals via highly conserved visceromotor mirroring systems ( 20 ) that include salience network structures such as the frontoinsula, anterior cingulate cortex, midcingulate cortex, and thalamus ( 34 37 ).…”
Section: Introductionmentioning
confidence: 99%